Managing stakeholders conflicts - Moura, Helder M. Pinto (2010)
It is not unusual that a chapter on conflict management, which is about, generally speaking, helping people or organizations that are in conflict with each other to deal with their differences, opens up with this statement (Moore, 1986 cited in Gordon, 1966): All societies, communities, organizations, and interpersonal relationships experience conflict at one time or another in the process of day-to-day interaction. Conflict is not necessarily bad, abnormal, or dysfunctional; it is a fact of life.